1978
DOI: 10.1177/009385487800500307
|View full text |Cite
|
Sign up to set email alerts
|

Self-Concept Changes Associated With Incarceration in Female Prisoners

Abstract: Changes in the self-concept associated with a period of incarceration were investigated. Female prisoners in the Iowa Women's Reformatory were administered the usual admissions test battery plus a 24-item Self-Concept Scale consisting of bipolar adjectives. When the same scale was readministered following a six-month period of incarceration, general improvement in the level of self-concept was evident. Moreover, some of the changes were related to personality characteristics, as measured by the MMPI, and educa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0
1

Year Published

1980
1980
1990
1990

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 12 publications
0
1
0
1
Order By: Relevance
“…Discrepant results were reported. Four studies (Bennett, 1974a;Gattshall, 1970;Gendreau, Gibson, Surridge, & Hug, 1973;Hannum, Borgen, & Anderson, 1978) found that inmates viewed themselves more favorably after months of confinement, whereas the other two studies suggested that self-concept either decreased (Fichtler, Zimmermann, & Moore, 1973) or remained unchanged (Nieberding, 1976). One study (Hepburn & Stratton, 1977) examined the relationship between self-esteem and sentence phase and suggested that fluctuations in selfesteem are more directly related to preprison and extraprison variables than they are to intraprison variables.…”
Section: Attitudinal Variablesmentioning
confidence: 99%
“…Discrepant results were reported. Four studies (Bennett, 1974a;Gattshall, 1970;Gendreau, Gibson, Surridge, & Hug, 1973;Hannum, Borgen, & Anderson, 1978) found that inmates viewed themselves more favorably after months of confinement, whereas the other two studies suggested that self-concept either decreased (Fichtler, Zimmermann, & Moore, 1973) or remained unchanged (Nieberding, 1976). One study (Hepburn & Stratton, 1977) examined the relationship between self-esteem and sentence phase and suggested that fluctuations in selfesteem are more directly related to preprison and extraprison variables than they are to intraprison variables.…”
Section: Attitudinal Variablesmentioning
confidence: 99%
“…Ωστόσο, τα αποτελέσματα σε σχέση με την καταστροφική επίδραση της φυλάκισης στην αυτοεκτίμηση είναι, στην καλύτερη περίπτωση, μικτά. Παρά κάποιες εμπειρικές μελέτες που υποστηρίζουν τον ισχυρισμό ότι ο εαυτός είναι μειωμένος κατά τη φυλάκιση (Hepburn & Stratton, 1977;Wormith, 1984), άλλοι συγγραφείς είτε δεν μπόρεσαν να ταυτοποιήσουν τέτοιο αποτέλεσμα, ή έχουν πράγματι βρει αντίθετα αποτελέσματα (Atchley & McCabe, 1968;Bennett, 1974;Bryson & Groves, 1989;Bukstel & Kilmann, 1980;Hannum, Borgen & Anderson, 1978;Power, 1990;Zamble & Porporino, 1988;Evans, Copus, Sullenberger, & Hodgkinson, 1996;Harter, 1990). Επιπλέον, αρκετές μελέτες πέρα από το στενό πλαίσιο της φυλάκισης και το στιγματισμό των ατόμων αποδεικνύουν ότι δεν παρατηρείται γενικά μείωση της αυτοεκτίμησης (Leary & Baumeister, 2000;Crocker & Quinn, 2000).…”
Section: επίδραση της άσκησης στην αυτοεκτίμηση των κρατουμένωνunclassified